Comparison between vitamin E plasma level in diabetic retinopathy and normal person - Tri Wahyu Widayanti Tri Wahyu Widayanti (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1997)
Diabetic retinopathy is one of the late complications of diabetes mellitus. Recent data have suggested that free radicals possibly play a role in its pathophysiology. Oxidative stress is very high in hyperglycemic condition leading to increased lipid peroxidation of the phospholipid cell membrane. Vitamin E is a chain breaking membrane antioxidant which can prevent lipid peroxidation in the cell membrane. The study was aimed at determining vitamin E plasma level in diabetic retinopathy compared to healthy subjects. In this study vitamin E plasma level in 30 diabetic retinopathy patients and 30 healthy subjects were measured by using (HPLC) technique. The result showed that the mean of vitamin E plasma level in healthy subjects and patients with diabetic retinopathy are 5.09 ± 3.51 and 4.32 ± 2.75 µg/ml respectively (Student t-test, p > 0.05) Total lipid level has a significant influence in increasing the vitamin E plasma level with coefficient correlation r=0.9746 and p<0.01. Further studies are needed to clasify factors that influence vitamin E plasma levels.Keywords: vitamin E - diabetic retinopathy - oxidative stress - lipid peroxidation